2010
DOI: 10.1177/1088868310377394
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Interventions to Reduce Loneliness

Abstract: Social and demographic trends are placing an increasing number of adults at risk for loneliness, an established risk factor for physical and mental illness. The growing costs of loneliness have led to a number of loneliness reduction interventions. Qualitative reviews have identified four primary intervention strategies: 1) improving social skills, 2) enhancing social support, 3) increasing opportunities for social contact, and 4) addressing maladaptive social cognition. An integrative meta-analysis of lonelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
1,376
6
22

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,490 publications
(1,461 citation statements)
references
References 154 publications
(241 reference statements)
57
1,376
6
22
Order By: Relevance
“…The literature on interventions aimed at preventing and coping with loneliness lays out four strategies: (a) improving social skills; (b) enhancing social support; (c) increasing opportunities for social contact; and (d) addressing maladaptive social cognition. Among these the latter was found to be the most successful intervention strategy (Masi et al 2011). Most recently, it has been proposed that integrated interventions which combine (social) cognitive behavioral therapy with short-term adjunctive pharmacological treatments are most effective in combating loneliness (Cacioppo et al 2015b).…”
Section: Resultsmentioning
confidence: 99%
“…The literature on interventions aimed at preventing and coping with loneliness lays out four strategies: (a) improving social skills; (b) enhancing social support; (c) increasing opportunities for social contact; and (d) addressing maladaptive social cognition. Among these the latter was found to be the most successful intervention strategy (Masi et al 2011). Most recently, it has been proposed that integrated interventions which combine (social) cognitive behavioral therapy with short-term adjunctive pharmacological treatments are most effective in combating loneliness (Cacioppo et al 2015b).…”
Section: Resultsmentioning
confidence: 99%
“…According to several studies (e.g., de Jong Gierveld & Havens, 2004;Killeen, 1998;Saari, 2009), loneliness is a socio-political question, and therefore, communal methods, distribution of information, and holistic culture of caring should be considered salient societal means of preventing problems such as loneliness. Although it is possible to arrange expensive and large societal and educational interventions to prevent loneliness (see e.g., Masi, Chen, Hawkley, & Cacioppo, 2011;VanderWeele et al, 2011), often the roots of loneliness can be found in childhood, friendships, and families (Uruk & Demir, 2003). Therefore, we want to spend a moment discussing the role of peer support.…”
Section: Resultsmentioning
confidence: 99%
“…This said, it is far from clear that cognitive-behavioural approaches can address precursors of loneliness such as bereavement, 113 and our research team shares the concerns of those who counsel against the medicalisation of commonplace experiences such as loneliness. 114,115 Even if one accepts the research findings of Masi et al, 112 financial constraints and policy decisions by state health providers mean that access to trained cognitive-behavioural therapists is limited and available only within stepped-care models for those with more serious mental health problems. 116 Given the ability of volunteers to faithfully deliver quite basic group facilitation, when trained within typical voluntary sector financial constraints, it seems unlikely that widespread and systematic access to more psychologically sophisticated behaviour change interventions is feasible for the alleviation of loneliness, even if they do have an impact.…”
Section: Other Studies Evaluating Interventions To Address Lonelinessmentioning
confidence: 99%